Relation of Changes in Body Satisfaction with Propensities for Emotional Eating Within a Community-delivered Obesity Treatment for Women: Theory-based Mediators - James J. Annesi (New Prairie Press, 2022)
Because of social pressures for thinness in women, body image/body satisfaction is often problematic. Although associations between body satisfaction, emotional eating, and changes in both have been proposed, they are not well-understood and might have implications for weight loss treatments. Women participants of a community-based obesity treatment (Mage = 41.4 years) with either high (n = 65) or normal (n = 79) propensities for emotional eating at baseline were measured on body satisfaction, eating-related self-regulation, dimensions of negative mood and emotional eating, exercise and eating behaviors, and weight at baseline and Months 3 and 6. The high emotional eating group had significantly higher scores on the negative mood and emotional eating measures, and significantly lower body satisfaction. However, that group demonstrated significantly greater improvements on those measures, and on the intake of fruits/vegetables and sweets, than the normal emotional eating group. Body satisfaction change was significantly predicted by exercise, weight, and eating measure changes, unaffected by group. Changes in body satisfaction significantly predicted changes in emotional eating. However, when changes in self- regulation and the mood measures were entered as sequential mediators, the overall mediation models were significant but not those relationships. Findings will inform obesity treatment targets and improve potentials for reductions in the health risks of participants.